2017
DOI: 10.1101/183467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of an integrated genomic map for a threatened Caribbean coral (Orbicella faveolata)

Abstract: Genomic methods are powerful tools for studying evolutionary responses to selection, but the application of these tools in non-model systems threatened by climate change has been limited by the availability of genomic resources in those systems. High-throughput DNA sequencing has enabled development of genome and transcriptome assemblies in non-model systems including reef-building corals, but the fragmented nature of early draft assemblies often obscures the relative positions of genes and genetic markers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…Previous work has suggested that the potential karyotype of O. faveolata is 16 chromosomes [48]. In our study, telomeric repeat analysis identified regions at either one (telocentric, 12 scaffolds) or both (metacentric, seven scaffolds) ends of 19 of the 51 scaffolds (TeloScafs) (Fig.…”
Section: Potential Chromosomes Are Recovered From Hifi Reads Without ...supporting
confidence: 51%
See 1 more Smart Citation
“…Previous work has suggested that the potential karyotype of O. faveolata is 16 chromosomes [48]. In our study, telomeric repeat analysis identified regions at either one (telocentric, 12 scaffolds) or both (metacentric, seven scaffolds) ends of 19 of the 51 scaffolds (TeloScafs) (Fig.…”
Section: Potential Chromosomes Are Recovered From Hifi Reads Without ...supporting
confidence: 51%
“…With the high percentage BUSCO completion of the telomere containing scaffolds, this further suggests that several scaffolds likely represent complete chromosomes. The number of identified TeloScafs is however larger than the potential karyotype of 16 for O. faveolata [48] suggesting that we missed some repetitive sections of the genome such as centromeric repeats. This may also be due to only utilizing HiFi reads for our assembly.…”
Section: Potential Chromosomes Are Recovered From Hifi Reads Without ...mentioning
confidence: 94%
“…Within the cnidaria, Orbicella (previously Montastrea) faveolata was the most often investigated organism. A wide range of sequencing data is available for this endangered reef-building coral, from whole-genome assemblies to RNA-seq data [50][51][52]. Notably, there is little information on proteomic, metabolomic, and multiomic responses within the cnidaria, indicating a knowledge gap for molecular responses in cnidaria beyond the transcriptional level (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…SNPs allow for targeted research into specific aspects of a species' ecology on the molecular level. Questions about the effectiveness of marine protected areas, organism's response to climate change and anthropogenic stressors as well as identification of genetically distinct populations, can be answered using SNPs technology [41,42]. SNP libraries can and have been developed for numerous species for conservation and management purposes.…”
Section: Analysis Of Risk Of Extinction Of Caribbean Biodiversitymentioning
confidence: 99%
“…SNP libraries can and have been developed for numerous species for conservation and management purposes. In the Caribbean, SNP technology has been applied across various taxa including endangered corals (Acropora palmata and Orbicella faveolata), fish (Nassau grouper), invertebrates (spiny lobster) and an invasive angiosperm (Halophila stipulacea) [42][43][44][45][46].…”
Section: Analysis Of Risk Of Extinction Of Caribbean Biodiversitymentioning
confidence: 99%